Thermal performance of an insulated roof with reflective insulation: Field tests under hot climatic conditions. (January 2013) - D'Orazio, Marco; Di Perna, Costanzo; Di Giuseppe, Elisa; Morodo, Matteo
The use of reflective insulation materials in buildings, for energy saving in summer, has been spreading in southern Europe. These products are not typical of the local building context. There is a lack of well-established measurement systems for reflective insulation thermal transmittance. The aim of this article is to understand whether a reflective insulation material could be effective in hot and temperate climate, also compared with other roof solutions. For this purpose, we compared the thermal performance of a roof with and without reflective insulation, both installed in a full-scale experimental building near Ancona (Italy) in the summer period. The results showed that the reflective insulation benefits are quite limited when using the insulation level imposed by actual laws, which consider insulation as the main strategy for energy saving in temperate and hot climates.